PEMIKIRAN TAMANSISWA TENTANG PENDIDIKAN BUDI PEKERTI PRA KEMERDEKAAN - Yuliati, Yuliati (Jurnal Sejarah dan Budaya, 2010)
Abstract: Tamansiswa is a cultural institution in the field of education. Founded by Suwardi Suryaningrat on 3 July 1922 and later known as Ki Hajar Dewantara, a multi talent person. In its curriculum, Tamansiswa gave balance between intelectual education, character and physical education. Character education was given to students of Tamansiswa because it has great benefits, especially for girls as their behavior guidance